Chaucer's Knight's Tale : An Annotated Bibliography 1900-1985 - McAlpine, Monica E., 1940- (Book collections on Project MUSE., 1991)
Monica McAlpine provides access to this material in the first of the Chaucer Bibliographies series to deal with a narrative portion of that author's best-known work.